2019
DOI: 10.3390/nu11050971
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intake, Sports Nutrition Knowledge and Energy Availability in Female Australian Rules Football Players

Abstract: This study aimed to assess nutritional intake, sports nutrition knowledge and risk of Low Energy Availability (LEA) in female Australian rules football players. Victorian Football League Women’s competition (VFLW) players (n = 30) aged 18–35 (weight: 64.5 kg ± 8.0; height: 168.2 cm ± 7.6) were recruited from Victoria, Australia. Nutritional intake was quantified on training days using the Automated 24 h Dietary Assessment Tool (ASA24-Australia), and sports nutrition knowledge was measured by the 88-item Sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
115
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(154 citation statements)
references
References 49 publications
(99 reference statements)
18
115
1
4
Order By: Relevance
“…Recent studies have investigated the prevalence of low EA in various sports [8,[13][14][15][16][17][18][19][20][21][22]. Prevalence ranges from 22% to 58% (Table 1).…”
Section: Low Energy Availabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have investigated the prevalence of low EA in various sports [8,[13][14][15][16][17][18][19][20][21][22]. Prevalence ranges from 22% to 58% (Table 1).…”
Section: Low Energy Availabilitymentioning
confidence: 99%
“…Another study investigating risk of low EA and sports nutrition knowledge among female Australian Rules football players reported that 30% of participants were at risk of low EA [8]. Nutrition knowledge of participants was measured using the Sports Nutrition Knowledge Questionnaire [65].…”
Section: Knowledge Of Low Energy Availability and Relative Energy Defmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be emphasized that this study did not have a large group, hence the results of this study may significantly differ from the others observed in the literature. Research conducted by showed that 30% of 27 women training football were at risk of low energy availability [10]. However, these studies only calculated the risk of low energy availability using the questionnaire method, they did not include energy expenditure measurement.…”
Section: Discussionmentioning
confidence: 99%